Tourism Development Strategy to Improve Community Economy Post Covid 19 Pandemic - Jaya, Rahmat; Suhaeb, M. Iqbal; Hidayat, Novit; Rasna, Rasna; Arifin, Herjuno Ariwibowo (PT Inovasi Pratama Internasional, 2025)
This research aims to examine the possibility of a tourism development strategy in improving the community's economy after the Covid 19 pandemic. This research uses a qualitative method by conducting a literature study. This type of research is a type of research by presenting a collection of data from various literatures that are closely related to the side of the world tourism development strategy in improving the economic sector of the post Covid-19 pandemic community. The data taken can be in the form of scientific journals, books, articles and other sources of information relevant to the research topic. In the literature review research method, researchers usually carry out the process of searching and collecting data through various sources of information. After that, the collected data are analyzed and evaluated to support the formulation of hypotheses, theoretical frameworks, or conclusions in the research and then draw red threads and conclusions. The results of this study concluded that tourism is a very important sector for Indonesia, both in terms of economy and cultural promotion to foreign countries. To revive tourism in East Java after the COVID-19 pandemic. The East Java Provincial Government has made various efforts, including: tourism promotion strategies through public relations strategies, development of tourism destinations with various facilities, cooperation with public development, tourism, with a marine base.